Kajian Pembelajaran Menggunakan Metode Proyek Based Learning dan Metode Demonstrasi di Kelas II SD Negeri 0723 Parmainan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to evaluate the implementation of Project-Based Learning (PjBL) and demonstration methods in learning activities in second-grade elementary schools. The PjBL method is implemented as an effort to increase active participation, creativity, and collaborative skills in students through the implementation of simple projects tailored to the developmental characteristics of elementary school-aged students. Meanwhile, the demonstration method is used to clarify learning concepts by directly displaying steps, processes, or concrete examples, making the subject matter easier for students to understand. The research approach used was descriptive qualitative, with data collection techniques including observations of learning activities, interviews with teachers and students, and supporting documentation. The results indicate that the implementation of the PjBL and demonstration methods can increase students' enthusiasm for learning, deepen their understanding of the subject matter, and encourage active student involvement in the learning process. Furthermore, the classroom atmosphere becomes more interactive and enjoyable. Thus, the PjBL and demonstration methods are considered effective and relevant in supporting meaningful and contextual learning in elementary schools, especially in the lower grades.